Ammonium iodide-induced sulfonylation of alkenes with DMSO and water toward the synthesis of vinyl methyl sulfones. Issue 1 (12th November 2014) - Gao, Xiaofang; Pan, Xiaojun; Gao, Jian; Huang, Huawen; Yuan, Gaoqing; Li, Yingwei
Abstract : A novel ammonium iodide-induced sulfonylation of alkenes with DMSO and water toward the synthesis of vinyl methyl sulfones is described. Abstract : A novel ammonium iodide-induced sulfonylation of alkenes with DMSO and water toward the synthesis of vinyl methyl sulfones is described. The process proceeded smoothly under metal-free conditions with high stereoselectivity and good functional group tolerance. The reaction mechanism was revealed to proceed through a domino reaction of oxidation and elimination after the radical addition to alkenes.